From investigations upon diagnosticity of characters for estimation of a degree of sexual dimorphism - Arska-Kotlińska, Małgorzata; Drozdowski, Zbigniew (Anthropological Review, 1984)
The authors have analysed a degree of sexual dimorphism of three descriptive traits using. material comprising candidates for physical education studies. It has been found that the highest diagnosticity is characteristic for a line of hair border along upper edge of the forehead, lower for hair border on the neck while the type of shoulder positioning shows 50% discordancy: with the actual sex of a subject.